The Challenges Experienced by International Nursing Students in Nursing Education: A Qualitative Study - Günay Arslan; Ece Karali; Hülya Elmalı Şimşek (Journal of Nursology)
Objective: The study aimed to determine the challenges experienced by international nursing undergraduate students during their education period.Methods: A phenomenological research design was used. The study was conducted with 20 international nursing students enrolled in a foundation university in Türkiye. Colaizzi's phenomenological data analysis method was employed in the study. Results: Based on the study’s results, three main themes, ‘Learning in a different environment’, ‘Challenges’, ‘Solution-Non Solution’ and ‘System difference, Language problems in clinical practice, Broad nursing curriculum, Facilitators, Language barrier, Feeling homesick, Racism and discrimination, Housing difficulties, Lack of funding, Instant solution, Failing to find a solution sub-themes themes were created. Conclusion: It has been observed that students experience different environments, uncertainties, and various challenges, and that these situations directly affect their education and success. To that end, both the institutions they receive education and the academicians must support the students in various ways.